2008
DOI: 10.1111/j.1540-6237.2008.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Mother Families and Air Pollution: A National Study*

Abstract: Objective-This study uses tract-level demographic data and toxicity-weighted air pollutant concentration estimates for the continental United States to determine whether (1) single-mother families are overrepresented in environmentally hazardous Census tracts and (2) the percentage of single-mother families in a Census tract is a significant predictor of tract-level toxic concentration estimates.Methods-After calculating tract-level toxic concentration estimates for the average female-headed family, male-heade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…Shifting into the children finding, this study finds that neighborhoods with higher percentages of children have higher levels of industrial hazard; this was also found in studies conducted in Sweden, Great Britain, and the US (Chaix et al 2006;Downey and Hawkins 2008;Mitchell and Dorling 2003). In terms of why children are disproportionately exposed to hazards at home, an explanation in the US relates to the location of public housing projects provided to a proportion of the poor.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Shifting into the children finding, this study finds that neighborhoods with higher percentages of children have higher levels of industrial hazard; this was also found in studies conducted in Sweden, Great Britain, and the US (Chaix et al 2006;Downey and Hawkins 2008;Mitchell and Dorling 2003). In terms of why children are disproportionately exposed to hazards at home, an explanation in the US relates to the location of public housing projects provided to a proportion of the poor.…”
Section: Discussionsupporting
confidence: 67%
“…While some studies have compared the social demographics of at-risk children and found them to be more often racial/ethnic minorities in south Florida (Chakraborty and Zandbergen 2007), less affluent in Sweden (Chaix et al 2006), and both (minority and/or low-income) in California (Houston et al 2006), others have used the concentration of children as an explanatory variable in predicting hazard, as we do here. Downey and Hawkins (2008) found in a national-level study (US) that single-mother families with young children were more concentrated in toxic neighborhoods than were any other family type; this variable was also a robust predictor of hazard across several statistical models. They tentatively propose that public housing and welfare policies may explain the concentration of single-mother families with young children in hazardous areas in the US, and they call for further studies to investigate why this pattern occurs (Downey and Hawkins 2008).…”
Section: Independent Variablesmentioning
confidence: 95%
See 3 more Smart Citations